ANTIBACTERIAL AND PHYTOCHEMICAL STUDIES OF Pteriocarpus erinaceus CRUDE EXTRACTS AGAINST DIARRHOEAGENIC Esherichia coli - MUHAMMAD, I. L.; MUHAMMAD, R. G.; KASSIM, J. Z.; MOHAMMED, A.; BABA, J.; DADI-MAMUD, N. J.; AMUZAT, A. O. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
The study was carried out to determine the antibacterial and phytochemical studies of Ptericarpus erinaceus extracts. The antibacterial assay was conducted using agar well diffusion method. The phytochemical screening was conducted using standard qualitative methods. The phytochemical screening of Ptericarpuserinaceus leaf extracts commonly contained alkaloids, flavonoids and steroids, while stem-bark extracts commonly indicated the presence of anthraquinones, glycosides, saponins and steroids. The bacteriaused were ten isolates (Escherichia coli) isolated from diarrhoeic stool of children 0-5 years. The result of Ptericarpus erinaceus crude leaf extracts showed appreciable inhibitory effect on all test isolates at 0.5-2.0 mg/ml concentration with zones of inhibition ranging from 8.00mm-22.00mm, while the entire isolates were resistance to hexane leaf extract. The stem-bark extracts inhibited the entire isolates at 0.5-2.0mg/ml concentration with zones of inhibition ranged between 8.00-30.00mm.The results has justified their utilization by the traditional medicine practioners for the treatment of ailments associated with the test isolates.